PENENTUAN PRODUK OLAHAN HASIL PERIKANAN UNGGULAN BERBASIS PESANTREN MENGGUNAKAN METODE FUZZY TOPSIS - Ramli Ramli; Budi Setiawan; Imam Santoso; Siti Asmaul Mustaniroh (Samakia : Jurnal Ilmu Perikanan, 2018)
Processed fishery products between one regions and other regions vary depending on the resources in the region which substantially increase added value for the fisheries sector as a whole. Thus the development of Processed fishery products in Situbondo Regency needs to pay attention to the potential of fishery resources and market potential in this region. Situbondo Regency is known as the city of santri because of the hundreds of pesantren with nearly one hundred thousand santri scattered in this area. Pesantren is a unique educational institution. One of the uniqueness is in the form of high militancy and fanaticism from santri, pesantren graduates, communities in pesantren and pesantren sympathizers. This high fanaticism can be converted into a potential market as a target market for processed fishery products at pesantren in Situbondo Regency. Therefore, a study is needed on the development of processed fishery products that can meet the market needs of pesantren in Situbondo. This research was conducted with the aim to determine of superior processed fishery products based on pesantren in Situbondo regency by using Fuzzy TOPSIS method, which is one of the fuzzy multi attribute methods for decision making. The results showed that superior processed fishery products based on pesantren in Situbondo regency were alternative A3 (squid crackers), processed fishery products of the next were alternative A1 (mixed fish crackers) and alternative A2 (tuna crackers).